2004
DOI: 10.1167/4.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of corneal horizontal/vertical astigmatism, lateral coma, and spherical aberration by internal optics of the eye

Abstract: Both the anterior surface of the cornea and the internal optics (the posterior cornea, crystalline lens) contribute to the aberration of a wavefront passing through the eye. Artal, Guirao, Berrio, and Williams (2001) reported that the wavefront aberrations produced by the internal optics offset, or compensate for, the aberrations produced by the cornea to reduce ocular wavefront aberrations. We have investigated the wavefront aberrations of the cornea, internal optics, and complete eye on both the population a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
149
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(166 citation statements)
references
References 23 publications
15
149
0
2
Order By: Relevance
“…This is in agreement with several recent studies on compensation of horizontal coma between the anterior cornea and internal optics. [10][11] This is also consistent with the theoretical account on relationship between spherical aberration and coma aberration in a previous study. 12 But, surprising to us was the non-significant correlations between the y-axis pupil center shift and the vertical coma.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with several recent studies on compensation of horizontal coma between the anterior cornea and internal optics. [10][11] This is also consistent with the theoretical account on relationship between spherical aberration and coma aberration in a previous study. 12 But, surprising to us was the non-significant correlations between the y-axis pupil center shift and the vertical coma.…”
Section: Discussionsupporting
confidence: 92%
“…The internal optics of the eye (posterior corneal surface and crystalline lens) directly oppose and reduce anterior corneal aberrations in normal eyes, 9,33,62,118,139 with compensation by the posterior corneal surface leading to an overall reduction in whole eye HOAs. Posterior corneal changes after EK affect its parallelism with the anterior corneal surface.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Kelly, Mihashi and Howland 15 used an instrument that allowed simultaneous capture of corneal and total eye aberrations on a population of young subjects. They found that some corneal aberrations are compensated by the internal optics of the eye, including horizontal/vertical astigmatism, lateral coma and spherical aberration.…”
Section: Corneal and Internal Astigmatismmentioning
confidence: 99%
“…12,15,16 The numerous studies into Javal's rule tend to indicate that this compensation is a passive process (that is, the majority of the population has approximately 0.5 D of internal astigmatism, opposite in sign to the corneal astigmatism). Some authors 15 have suggested the possibility of an active 'feedback driven' process operating to reduce the total astigmatism of the eye (particularly horizontal/vertical astigmatism).…”
Section: Corneal and Internal Astigmatismmentioning
confidence: 99%